CYBERBULLYING PADA ANAK SEKOLAH DASAR: STUDI FENOMENA DI ERA DIGITAL - Iswandi; Nasution, Soibatul Aslamiah; Citrowati, Endang; Dina Septiana, Yulda; Salman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Cyberbullying among elementary school children is a phenomenon that is increasing along with the development of digital technology and the intensity of social media use by children. Cyberbullying not only takes the form of insults or ridicule, but can also include social exclusion, dissemination of personal content, and collective pressure through comments and sharing features that amplify the impact on victims. This study aims to analyze the phenomenon of cyberbullying among elementary school children in the digital age through a combined approach of Systematic Literature Review (SLR) and social media analysis. Research data was obtained from literature synthesis through the selection of relevant scientific articles and content analysis on TikTok, YouTube, Instagram, and Facebook platforms. The results show that cyberbullying is formed through the interrelationship between individual factors (children's emotional and empathy development), social factors (peer influence and peer pressure culture), and digital system factors (platform algorithms, anonymity, and content virality). The findings from SLR confirm that cyberbullying affects children's psychological, social, and academic aspects, while social media analysis shows that bullying is normalized and reinforced by audience responses in the form of likes, comments, and shares. This study concludes that cyberbullying among elementary school children is a multidimensional problem that requires comprehensive prevention through strengthening digital literacy, character education, school and parent involvement, and the formation of a healthy communication culture in the digital space.